Estudo da microestrutura dos aços inoxidáveis austeníticos AISI 316L e 317L soldados pelo processo TIG - Pereira, Karla Guimarães Santos (2019)
Stainless steels were developed in the beginning of the 20th century and have been constantly improved since then. As other metal alloys, stainless steels are classified according to the chemical composition Austenitic stainless steels represent 2/3 of the world's stainless steel production due to their resistance to corrosion, oxidation, hot mechanical strength, workability and weldability. These properties are obtained by the addition of different alloying elements. In industry, the welding process is one of the most applied in austenitic stainless steels. Both the alloying elements and the different processes have a direct influence on the microstructure of the steel. The austenitic stainless steels present predominantly austenitic microstructure, but during solidification this structure is altered due to the formation of delta ferrite, derived from the segregation of stabilizing elements of the ferrite. The quantification of delta ferrite is extremely important for properties related to ductility, crack susceptibility and mechanical resistance. In addition, intermetallic phases, such as sigma, precipitates from the delta ferrite . There are several types of reagents used to perform chemical / electrolytic etching to reveal these phases in the microstructure. This work studied a methodology for the microstructural characterization of AISI 316L and AISI 317L austenitic alloys, welded by the GTAW process and submitted to heat treatments with different times, in order to reveal δ ferrite and intermetallic phases, sigma ( σ), chi (χ) and the Laves phase (η). AISI 316L and AISI 317L alloys were selected because they are characteristics for applications requiring high corrosion resistance. Both AISI 316L and AISI 317L alloys were solubilized at 1080 ° C with different times. Samples of both materials were analyzed in the base metal and in the weld metal, in the condition of welding and without heat treatment. According to Vander Voort electrolytic etching using the reactants in the proportions: 10% of oxalic acid, 10% KOH and 20% NaOH, all subjected to a voltage of 6V for 60s, reveal ferrite δ and some intermetallic phases such as sigma phase. In addition, a study on pitting corrosion was carried out by the potentiodynamic cyclic polarization method. It was concluded as well as the bibliographical references that the presence of intermetallic phases directly affects the resistance to pitting corrosion. The samples without heat treatment presented higher percentage of delta ferrite and were more resistant to pitting corrosion.